Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.31584/jhsmr.2022864
|View full text |Cite
|
Sign up to set email alerts
|

Good Medication Adherence and its Association with Meaning in Life among Thai Individuals with Schizophrenia

Abstract: Objective: To study medication adherence, meaning in life, the association of medication adherence and meaning in life among Thai individuals with schizophrenia.Material and Methods: This cross-sectional study surveyed all outpatient individuals with schizophrenia that followed up at the Psychiatric outpatient clinic, Songklanagarind Hospital. Three questionnaires were used:1) Demographic information 2) Medication adherence questionnaire and 3) The meaning in life questionnaire. Descriptive statistics were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A previous study from our Department of Psychiatry identified that most individuals with schizophrenia had good medication adherence and perceived their lives as meaningful [ 29 ]. Most of them, as well as their caregivers, perceived a low level of stigma [ 39 ] and a moderate quality of life [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study from our Department of Psychiatry identified that most individuals with schizophrenia had good medication adherence and perceived their lives as meaningful [ 29 ]. Most of them, as well as their caregivers, perceived a low level of stigma [ 39 ] and a moderate quality of life [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire demonstrated a sensitivity of 85.8; and a specificity of 89.7; a positive predictive value of 90.6; a negative predictive value of 84.7; Cronbach’s alpha coefficient of 0.828 [ 27 ]. The MAST has been utilized as a tool for measuring medication adherence in individuals with diabetes [ 27 ], hypertension [ 28 ], and psychiatric disorders [ 29 , 30 ]. 4.…”
Section: Methodsmentioning
confidence: 99%